If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + 9k = -5 Solving 4 + 9k = -5 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 9k = -5 + -4 Combine like terms: 4 + -4 = 0 0 + 9k = -5 + -4 9k = -5 + -4 Combine like terms: -5 + -4 = -9 9k = -9 Divide each side by '9'. k = -1 Simplifying k = -1
| 6w-2=2w+58 | | 9v^2-30v-25=0 | | 8x=16/7 | | D=26/pi | | http://media1.acellus.com/Library/00001022_223_A1.gif | | 56+8m=128 | | 4y^2+17y-15= | | 14y+1=1y+27 | | n-17=-13 | | 17n-70=168 | | 8x-10=8x-6 | | 42=4x+2x | | 4a+1=1a+25 | | f(x)=0.15x+5 | | 8y-5y=27 | | 5/3x-1=6/5x | | 6(x+30)=90 | | 8z-6=58 | | 5z+5=40 | | .2x+.6y=.52*80 | | 25=X+X+6 | | 1.5(x-4)=9.2 | | Y=3/4(x-3/4) | | Y=x(x+20) | | 3a^3/4-2a^3/4 | | 3y+2y+y+9x= | | 2n^2+4n-16=0 | | (3x-4)(-7x+4)=0 | | 2/(3-i) | | -4+4x=-8+10 | | -3(s+3)+10=8 | | 3x-18=y |